'Let us teach our children': Online racism and everyday far-right ideologies on TikTok. - Ozduzen, Ozge; Ferenczi, Nelli; Holmes, Isabel (Visual Studies, 2023)
This paper identifies perceptions of injustice, grievance, and alienation as online drivers of radicalisation by concentrating on contemporary visual radicalisation patterns. It focuses on far-right agents of radicalisation in the UK with a particular analysis of visual and ephemeral drivers of radicalisation on social media platforms. We analysed widespread TikTok hashtags which embody mainstream right-wing ideologies. Using these hashtags, we selected four popular videos (> 30k views) for visual thematic analysis of their compositional content and comment-sphere to explore everyday representations and discourses of far-right ideologies. Our findings highlight mundane online expressions on TikTok that collectively reinforce notions of a shared idealised identity built on nostalgic reinterpretations of an imperial past, which contribute to the mainstreaming of far-right ideas and ideologies.